Microfluidic solvent extraction of rare earth elements - Kriel, F.; Kolar, E.; Sedev, Rossen; Catthoor, R.; Middlemas, S.; Klier, E.; Hatch, G.; Priest, C. (2016)
© 2016 TAPPI Press. All rights reserved. This paper reports solvent extraction of rare earth elements (REEs) carried out using a microfluidic device and considers the REE loading limit of the organic phase under laminar flow. The microfluidic device contacts aqueous and organic phase streams for a precisely defined contact time (sub-second resolution) and then separates them for offline analysis. Experiments are reported examining the effect of contact time on extraction. We focus on three REEs: one ‘light’ (Nd), one ‘mid’ (Dy), and one ‘heavy’ (Yb) REE, which are extracted using Cyanex®572. It appears that loading limits may be locally exceeded in the organic phase near to the liquid-liquid interface, where third phase deposits are observed. Third phase formation was also observed close to the liquid-liquid interface in two-dimensional confinement, showing similar third phase adsorption on glass plates. It is also shown that, under microfluidic flow, a typical first ‘split’ between heavy REEs and light REEs can be carried out without exceeding loading limits.